Changes in Moisture Sources of Atmospheric Rivers Landfalling the Iberian Peninsula With WRF‐FLEXPART. Issue 8 (26th April 2023) - Fernández‐Alvarez, J. C.; Pérez‐Alarcón, A.; Eiras‐Barca, J.; Ramos, A. M.; Rahimi‐Esfarjani, S.; Nieto, R.; Gimeno, L.
Abstract: This paper makes use of a combination of FLEXPART‐WRF simulations forced with ERA5 and the CESM2 model—incorporated in the CMIP6 project—to infer a series of changes over the present century in the behavior of the landfalling atmospheric rivers (ARs) arriving to the Iberian Peninsula. In addition, future changes in the intensity and position of their main moisture sources are studied. In overall terms, there is a noticeable increase in the amount of moisture transported by ARs in the study region, particularly accentuated by the end of the century. However, no significant changes in the number of events are observed. A northward shift of both the mean position of the ARs as well as their main sources of moisture is also detected, particularly for the end of the century, and in the summer and fall months. In relation to the latter, an increase in the contribution of moisture contribution is also observed, quantitatively compatible with Clausius‐Clapeyron amplification. Plain Language Summary: This paper makes use of a combination of simulations forced with reanalysis data and a climate model to infer a series of changes over the present century in the behavior of the landfalling atmospheric river—ARs, regions of intense moisture transport located in the lower layers of the atmosphere—arriving at the Iberian Peninsula. In addition, future changes in the intensity and position of their main moisture sources are studied. In overall terms, there is a noticeable increase in the amount of moisture transported by ARs in the study region, particularly accentuated by the end of the century. However, no significant changes in the number of events are observed. A northward shift of both the mean position of the ARs as well as their main sources of moisture is also detected, particularly for the end of the century, and in the summer and fall months. In relation to the latter, an increase in the contribution of moisture contribution is also observed, in a ratio similar to that expected. Key Points: FLEXPART‐WRF forced with CESM2 model has been able to reproduce the historical conditions of Atmospheric River over the Iberian Peninsula A northward shift of the main source regions is projected, notable in summer and fall and particularly by the end of the century Gradual strengthening in the intensity of Atmospheric Rivers is expected, observable from an increase in the amount of moisture transported